Determinan Indeks Pembangunan Manusia Provinsi DKI Jakarta Tahun 2010-2021 - Safrilina Husnun Nisa; Nugroho Sumarjiyanto Benedictus Maria (Diponegoro Journal of Economics, 2022)
This study aims to determine the effect of the poverty rate, unemployment rate, and labor force participation rate on the human development index of DKI Jakarta. This study was conducted to find out whether or not those variables are indeed three factors that played an important role in encouraging DKI Jakarta to have the highest human development index among 33 other provinces in Indonesia. This study used panel data from 6 administrative districts and cities in DKI Jakarta during 2010-2021 using a random effect panel regression model. The results showed that there was a significant negative effect of the poverty rate and the open unemployment rate on the human development index. Meanwhile, the labor force participation rate has a significant positive effect on the human development index of DKI Jakarta during 2010-2021. According to the F-statistic, it showed the human development index simultaneously affected by the poverty rate, open unemployment rate, and labor force participation rate within 60% R-squared. This study specifically highlights economics and employment in DKI Jakarta as aspects with the most programs and policies applied.